Keabsahan Kontrak Elektronik Dalam Layanan Pinjam Meminjam Uang Berbasis Teknologi Informasi - Lintang Cahyani Andira; Iswi Hariyani (Faculty of Law, University of Jember, Indonesia, 2020)
One of the advances in the digital economy today is the adaptation of technology in the financial sector, also known as Financial Technology (Fintech). This financial technology will shift the conventional financial industry by reason of the high demands of society. One of the fintech products is the provision of information technology-based lending and borrowing services (Peer to Peer or P2P Lending). The flow of fintech shifts the trading transaction system, which was originally paper-based, to a non-paper-based (digital) transaction system. The parties involved themselves in economic transactions which were originally bound using conventional contracts, turned into electronic contracts. Legal issues arise regarding the legal validity of conventional contracts which are translated into electronic form. Therefore, it is necessary to study the validity of this electronic contract further as the basis for the engagement between the two parties that enter into an information-based lending and borrowing service.